Adult Education: A Tool for Rural Transformation in Nigeria - Orobor, M. E.; Ejiro-Mitaire, F. O. (Journal of Research in Adult and Continuing Education, 2024)
Interest in rural development in recent times has continued to gather momentum, particularly in developing economy like ours, because majority of the people live and find their means of livelihood in the rural areas. This paper examined the issue of how the rural areas can be transformed through adult education, by exploring scholars’ views and opinions on issues through extensive review of literature and philosophical analysis. The discussion opened with an explanation of the concepts of rural area; rural transformation; and, adult education. The socio-psychological issues to consider in planning educational programme for the rural populace was also examined while emphasizing on characteristics of the rural dwellers which influence the programme designed for them. The discussion climaxed with an exploration of how the rural areas can be transformed through adult education. The discussion was anchored on the fact that adult education aims at re-orientating the valued systems and ideology of the rural people, the philosophy of rural dwellers about the totality of their existence. The central argument of the paper is that, with proper conscientization of the rural dwellers through adult education, they will be in a better position to contribute to the upliftment of their Communities.
Keywords: Rural area; adult education; rural transformation